Penguatan Pendidikan Akhlak pada Pendidikan Dasar/MI - Suparlan Suparlan (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
ABSTRACT (ENGLISH) Education is a conscious and planned effort in the process of mentoring and learning for individuals so that they grow and develop into human beings who are independent, responsible, creative, knowledgeable, healthy and have noble character (UU No.20 of 2003). While the purpose of education in Law no. 20 of 2003 concerning the National Education System is: National Education functions to develop capabilities and shape dignified national character and civilization in order to educate the nation's life, aims to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible country”. Morals come from the Arabic plural 'from the mufradat form "khuluqun" which means manners, temperament, behavior and character. Meanwhile, according to the term is knowledge that explains good and bad (right and wrong), regulates human interaction, and determines the ultimate goal of his business and work. ABSTRAK (INDONESIA) Pendidikan adalah upaya sadar dan terencana dalam proses pembimbingan dan pembelajaran bagi individu agar tumbuh berkembang menjadi manusia yang mandiri, bertanggung jawab, kreatif, berilmu, sehat dan berakhlak (berkarakter) mulia (UU No.20 tahun 2003). Sedangkan tujuan pendidikan dalam Undang-Undang No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional adalah: Pendidikan Nasional berfungsi mengembangkan kemampuan dan membentuk watak serta peradaban bangsa yang bermartabat dalam rangka mencerdaskan kehidupan bangsa, bertujuan untuk berkembangnya potensi peserta didik agar menjadi manusia yang beriman dan bertakwa kepada Tuhan Yang Maha Esa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab”. Akhlak berasal dari bahasa Arab jama’ dari bentuk mufradatnya“khuluqun” yang berari budi pekerti, perangai, tingkah laku dan tabiat. Sedangkan menurut istilah adalah pengetahuan yang menjelaskan tentang baik dan buruk (benar dan salah), mengatur pergaulan manusia, dan menentukan tujuan akhir dari usaha dan pekerjaannya.